Assessing costs of a hypertension management program: An application of the HEARTS costing tool in a program planning workshop in Thailand. Issue 1 (24th December 2019) - Husain, Muhammad Jami; Allaire, Benjamin T.; Hutchinson, Brian; Ketgudee, Lalida; Srisuthisak, Sasamon; Yueayai, Khanuengnij; Pisitpayat, Nichakul; Nugent, Rachel; Datta, Biplab Kumar; Joseph, Kristy T.; Kostova, Deliana
Abstract: The HEARTS technical package, a part of the Global Hearts Initiative to improve cardiovascular health globally, is a strategic approach for cardiovascular disease prevention and control at the primary care level. To support the evaluation of costs associated with HEARTS program components, a costing tool was developed to evaluate the incremental cost of program implementation. This report documents an application of the HEARTS costing tool during a costing workshop prior to the initiation of a HEARTS pilot program in Thailand's Phothong District, 2019‐2020. During the workshop, a mock exercise was conducted to estimate the expected costs of the pilot study. The workshop application of the tool underscored its applicability to the HEARTS program planning process by identifying cost drivers associated with individual program elements. It further illustrated that by supporting disaggregation of costs into fixed and variable categories, the tool can inform the scalability of pilot projects to larger populations. Lessons learned during the initial development and application of the costing tool can inform future HEARTS evaluation efforts.